(13-x)-4=3

Simple and best practice solution for (13-x)-4=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (13-x)-4=3 equation:


Simplifying
(13 + -1x) + -4 = 3

Remove parenthesis around (13 + -1x)
13 + -1x + -4 = 3

Reorder the terms:
13 + -4 + -1x = 3

Combine like terms: 13 + -4 = 9
9 + -1x = 3

Solving
9 + -1x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + -1x = 3 + -9

Combine like terms: 9 + -9 = 0
0 + -1x = 3 + -9
-1x = 3 + -9

Combine like terms: 3 + -9 = -6
-1x = -6

Divide each side by '-1'.
x = 6

Simplifying
x = 6

See similar equations:

| 4z^2+5=167 | | 1004x-x^2=234315 | | X^2+2y^2-3.5xy=0 | | 45-6x+7x=68 | | -1x+3x=18 | | 489x-0.5x^2=110980 | | 5x-(4x-23)=67 | | (4x-5)(3x+1)-(6x+2)(x+2)=0 | | 6*(2+2)+5*(3+8)=41 | | 676000=6000X+40000 | | 6*2+(2+5)*3+8=41 | | 6*(2+2)+(5*3+8)=41 | | 76-5x=9x-20 | | (6*2+2)+(5*3+8)=41 | | (6*2)+2+(5*3+8)=41 | | 6*2+2+(5*3+8)=41 | | 6*2+2+5*3+8= | | 6*(2+2+5)*3+8=41 | | 6*2+2+5*(3+8)=41 | | 6*(2+2)+5*3+8=41 | | (6*2)+2+5*3+8=41 | | 6*2+2+5*3+8=41 | | 58+4x=10x-2 | | 4x^2+28x=-4 | | 5n+7= | | x-4=20-2x | | 3x^2-22x+288=0 | | 8n-4= | | 3x^2-22+288=0 | | 5n+3=62 | | 2x-7=4x-5 | | 83-7x=20x+20 |

Equations solver categories